2023
DOI: 10.3390/a16060308
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Heart Disease Prediction through Ensemble Learning Techniques with Hyperparameter Optimization

Daniyal Asif,
Mairaj Bibi,
Muhammad Shoaib Arif
et al.

Abstract: Heart disease is a significant global health issue, contributing to high morbidity and mortality rates. Early and accurate heart disease prediction is crucial for effectively preventing and managing the condition. However, this remains a challenging task to achieve. This study proposes a machine learning model that leverages various preprocessing steps, hyperparameter optimization techniques, and ensemble learning algorithms to predict heart disease. To evaluate the performance of our model, we merged three da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…However, data used for this study 49 was very limited (only 303 records were used in this study). Following, a study conducted by Asif et al 50 precision and specificity were reported as 95.08 and 98.09, respectively. However, the analysis 50 was tested on very limited data (only 1625 records were used in this study).…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…However, data used for this study 49 was very limited (only 303 records were used in this study). Following, a study conducted by Asif et al 50 precision and specificity were reported as 95.08 and 98.09, respectively. However, the analysis 50 was tested on very limited data (only 1625 records were used in this study).…”
Section: Literature Reviewmentioning
confidence: 98%
“…While a model may perform well in balanced circumstances, it might struggle in imbalanced situations in real life 26,27 . To truly assess the effectiveness of proposed approaches 48,49,50 , it is crucial to test them in unbalanced scenarios using a larger number of samples. The performance measurements across various unbalanced circumstances should be thoroughly described in order to appropriately assess the success of the suggested approaches in real-life situations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Through bootstrapping, distinct subsets of the training data are created by random sampling with replacement from the original dataset. This helps in reducing overfitting by providing a more robust and generalizable model [42,43]. At each node of the decision tree, a random subset of features is considered for each split instead of using all features for each split.…”
Section: Machine-learning (Ml) Modelsmentioning
confidence: 99%
“…This helps in decorrelating the trees and introduces diversity in the ensemble. The RF algorithm involves the tuning of multiple hyperparameters, including the n estimators (count of decision trees for growth in the forest), max depth of each decision tree in the forest, criterion (a function used to evaluate split quality at each node of the trees, for example, Gini impurity and information entropy) [42]. More trees in the forest generally results in more reliable and accurate predictions [43].…”
Section: Machine-learning (Ml) Modelsmentioning
confidence: 99%